Closure IS change. Change takes time and needs support. It's a smouldering fuse, not a 'burning platform' - Getty, R. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Closure IS change. When a mine ramps down and ceases to operate, it is a change that happens whether we plan for it or not, to the company and workforce, the environment, and future land users. Unplanned change results in unforeseen outcomes that force a new direction. To leave a positive legacy for closure we need to plan for change, which takes time. We need time to ask questions and gain knowledge, to understand what land capability is needed for the post-closure vision. We need time to identify and discuss options, design and co-design the legacy we want to leave, starting as early as possible. This relies on meaningful engagement with our partners in changewho are people that have differing views. Significant change can invoke grief, with different emotions at each stage needing time for adaptation. Right from the start, we need to collaborate and integrate closure with the mine life plan with all disciplines and functions. This is not new. It was acknowledged in the late 1990s by the World Bank and in 2000 by the Mining, Minerals and Sustainable Development project and is still discussed now as one of the main challenges to closure. Integration is not easy. It needs culture, supporting processes, trust and based on shared language and goals. A typical change management phrase uses a 'burning platform' to drive urgent change through fear or reaction to something unfavourable. But a burning platform for closure means we're too late. We've run out of time, we don't have options, and our legacy will be 'what's left' rather than our vision. Closure is the smouldering dynamite fuse, and if we don't plan and integrate closure early and throughout the entire mine lifecycle, we can be left with an expensive surprise. At BHP, we recently updated our global standard for closure. BHP requirements for Closure and Legacy Management took eight months to develop. Our objective was to collaborate, support early integration, and emphasise the interconnectedness of closure. We embedded closure language in BHPs Master Glossary and defined time, including the Life of Asset' "… until BHP no longer holds liabilities." This paper describes the process and key lessons learned along the way. What legacy do you want to leave?